Meta-analysis of Therapeutic Effect in Depression Treatment of Repetitive Transcranial Magnetic Stimulation Combined Paroxetine - Xinyi GUO; Guo YU; Xiaokuo HE (康复学报)
Objective:To evaluate the therapeutic effect of repetitive transcranial magnetic stimulation(TMS)combined with paroxetine in the treatment of depression, provide reference for the clinical treatment and related research of depression.Methods:We electronically searched databases, including CNKI Chinese Journal Full-text Database, Wanfang Database, VIP Database, PubMed, the Cochrane Library and EMbase, to collect randomized controlled trials(RCTs)about depression treated by repetitive TMS combined with paroxetine. The time limitation was from the establishment of each database to 31st August 2017.Two reviewers independently screened literature, extracted data and assessed the risk of bias of the included studies. Then, Meta-analysis was performed by using RevMan 5.3 software.Results:A total of sixteen related articles and 1 150 patients were retrieved. The effective rate was selected as primary outcome measure in five articles, and Meta analysis showed that compared with control group, pooled RR was 1.35 with 95%CI [1.11, 1.65], Z=3.00, P<0.01, in the test for overall effect, implying the significant effective rate difference between the two groups was in the treatment of first-episode depressive. The adverse reaction rate was selected as primary outcome measure in five articles. Meta analysis showed that compared with control groups, pooled RR was 0.83 with 95%CI [0.56, 1.24], Z=0.92, P>0.05, in the test for overall effect, implying that the adverse reaction rate difference of two groups was not significant. The HAMD scores was selected as secondary outcome measure in three articles, and Meta analysis showed that compared with control groups, pooled MD was-1.71 with 95%CI [-4.82, 1.40], Z=1.08, P>0.05, in the test for overall effect, implying that the HAMD scores difference of two groups was not significant. The effective rate was selected as primary outcome measure in five articles. Meta-analysis showed that compared with control groups, pooled RR was 1.20 with 95%CI [0.96, 1.52], Z=1.58, P>0.05, in the test for overall effect, implying the effective rate difference of two groups was not significant in the treatment of depressive. The adverse reaction rate was selected as primary outcome measure in four articles, and Meta-analysis showed that compared with control groups, pooled RR was 0.96 with 95%CI [0.68, 1.34], Z=0.26, P>0.05, in the test for overall effect, implying the adverse reaction rate difference of two groups was not significant in the treatment of depressive. The HAMD scores were selected as secondary outcome measure in eight articles, and Meta analysis showed that compared with the control group, pooled MD was-3.26 with 95%CI [-3.83, -2.69], Z=11.20, P<0.01, in the test for overall effect, implying that the HAMD scores difference of two groups was significant in the treatment of depressive.Conclusion:The effect of repeated TMS combined Paroxetine in the treatment of first-episode depressive disorder and depression is better than Paroxetine with and without pseudo stimulus, but there is no difference in side effects. Therefore, repeated TMS combined paroxetine may be more suitable for clinical use in the treatment of first-episode depression and depression. However, the above conclusion still needs to be verified by large sample and high quality RCTs.